BRACKISH WATER DESALINATION BY NANOFILTRATION – EFFECT OF PROCESS PARAMETERS - COLLANA, JUAN MEDINA (2024)
BRACKISH WATER IS AN IMPORTANT SOURCE OF WATER RESOURCES WITH LOWER SALT CONTENT THAN SEAWATER. DESALINATION IS A VERY IMPORTANT TREATMENT TO REMEDY THE SCARCITY OF FRESH WATER THROUGHOUT THE WORLD. IN THIS WORK, IT HAS BEEN PROPOSED TO DESALINATE BRACKISH GROUNDWATER USING A COMMERCIAL NANOFILTRATION MEMBRANE. THE EXPERIMENTS WERE CARRIED OUT ON THE BASIS OF A FACTORIAL DESIGN USING THREE FACTORS AND TWO LEVELS OF STUDY FOR EACH VARIABLE. FOR THIS PURPOSE, IT SELECTED THE FEED PRESSURE (X1) OF THE MEMBRANE MODULE AT (60 AND 100 PSI), FEED WATER SALINITY (X2) AT LEVELS OF (3.4 AND 6.01 MS/CM) AND OPERATING TEMPERATURE (X3) AT LEVELS (20 AND 28 °C) TO EVALUATE ITS EFFECT ON THE PERCENTAGE FLUX RECOVERY AND SALT RETENTION. THE RESULTS SHOWED THAT THE MOST SIGNIFICANT VARIABLE IS THE FEED PRESSURE, ACHIEVING HIGHER FLOW RECOVERY AND THE PERCENTAGE OF SALINITY REJECTION AT THE 100 PSI LEVEL. THIS SHOWED THAT BY INCREASING THE PRESSURE FROM (60 TO 100 PSI), THERE WAS A CONSIDERABLE INCREASE IN FLOW RECOVERY (42 TO 72%) AND SALT REJECTION (24.6 TO 28.4%). LIKEWISE, BY INCREASING THE TEMPERATURE FROM 20 TO 28 °C, THE RECOVERED FLOW RATE INCREASED FROM (49.78 TO 63.2%) AND THE PERCENTAGE OF SALT SEPARATION SHOWED AN INCREASE FROM 25.95 TO 27.05%. SIMILARLY, BY INCREASING THE STARTING CONDUCTIVITY OF THE BRACKISH WATER FROM (3.4 TO 6.01 MS/CM) THE PERCENTAGE OF FLOW RECOVERY HAS DECREASED FROM (61.46 TO 51.525%). LIKEWISE, THE PERMEATE FLOW RATE INCREASED LINEARLY WITH FEED PRESSURE FROM 132 L/H (P = 40 PSI) TO 420 L/H (108 PSI). IN CONCLUSION, THIS RESEARCH CONFIRMS THE SUITABILITY OF THE COMMERCIAL NF MEMBRANE STUDIED FOR BRACKISH WATER DESALINATION. © (2024), (POLISH SOCIETY OF ECOLOGICAL ENGINEERING (PTIE)). ALL RIGHTS RESERVED.